Detective Critics and Murderous Critics. The Search for a Manuscript in South American Detective Novels (1990-2006) - Pellicer, Rosa (Anales de Literatura Hispanoamericana, 2008)
The «classic» detective model has been notably revitalised in the last fifteen years in Spanish America. This articule studies the subject of the «search for a manuscript» in an important group of works which are not strictly detective novels, by Sergio Gómez, Jorge Manzur, Pablo de Santis and Alejandro Vaccaro, as well as others which make deft use of the theme of literary research as one of the principle lines of the narration, as is the case in novels by Leonardo Padura, Juan José Saer and Roberto Bolaño.